Cervical radiculopathy and spinal cord indentation caused by vertebral artery loop - HARMAN, FERHAT; ALTUNTAŞ, DOĞUKAN; GÜVENÇ, YAHYA; KURŞUN, MELTEM (My University, 2022)
Cervical radiculopathy and spinal cord indentation caused by vertebral artery loop formation is a rare entity. We report here an 85-year-old woman had a four-year history of neck pain and left arm weakness. Radiologic evaluation showed vertebral artery loop formation compressing the adjacent nerve root and spinal cord. Accurate radiologic diagnosis of this condition is crucial to reduce unexpected surgical complications.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Nöroloji; Medicine; Health Sciences; Internal Medicine Sciences; Neurology; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Neurology (clinical); Life Sciences